1990
DOI: 10.1172/jci114821
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of hereditary C3 deficiency.

Abstract: Hereditary deficiency of complement component C3 in a 10-yr-old boy was studied. C3 could not be detected by RIA of serum from the patient. Segregation of C3 S and C3 F allotypes within the family confirmed the presence of a null gene for C3, for which the patient was homozygous. 30 exons have been characterized, spanning the entire ft chain of C3 and the a chain as far as the C3d region. Sequence analysis of the exons derived from the C3 null gene showed no abnormalities in the coding sequences. A GT-AT mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 32 publications
0
22
0
2
Order By: Relevance
“…Infections tend to be recurrent and severe. Invasive infections (meningitis, bacteremia, pneumonia, and otitis media) with S. pneumoniae, N. meningitidis, and H. influenzae have been reported (41,43,119,132,172,184,340,386,451).…”
Section: Inherited Deficiencies Of Complement Activationmentioning
confidence: 99%
“…Infections tend to be recurrent and severe. Invasive infections (meningitis, bacteremia, pneumonia, and otitis media) with S. pneumoniae, N. meningitidis, and H. influenzae have been reported (41,43,119,132,172,184,340,386,451).…”
Section: Inherited Deficiencies Of Complement Activationmentioning
confidence: 99%
“…20 Following the description of the genomic structure of C3 in 1990, 21 a molecular basis for C3 deficiency was first described. 22 Subsequently, inherited C3 deficiency has been identified in 19 families (reviewed in Reis et al 23 ) and the underlying molecular mechanism established in 8 of these. In this study we have identified 9 heterozygous mutations in C3.…”
Section: Org Frommentioning
confidence: 99%
“…Failure to use the normal splice site resulted in the use of a cryptic site within the adjacent downstream exon, leading to an internal deletion and frameshift in the mRNA. Use of the altered reading frame generated a premature stop codon downstream from the cryptic splice site and resulted in the production of a truncated nonfunctional C3 protein (36).…”
Section: Microbial Interactions With Complementmentioning
confidence: 99%